(untitled) (Historia, 2021)
Karel Schoeman, generally thought of as one of South Africa’s foremost Afrikaans authors, has long been instrumental in writing South African history based on primary source material in a way which promotes the accessibility of this material. His career as a historian extends back several decades, and includes his own master’s dissertation on Botswana’s foreign policy in the twentieth century. In his work he primarily concentrated on editing and presenting restricted circulation archival texts, in Afrikaans, Dutch and English. As an archivist in the Free State, he was responsible for compiling, writing and presenting a series of works on the early history of the area. He continued this tradition at the South African Library until his recent retirement. As well as this work, he has produced several more substantial historical pieces, including a notable biography of Olive Schreiner. One of the most recent of his extensive works is Dogter van Sion, an examination of eighteenth-century Dutch society, refracted through the experiences of Machtelt Smit, missionary and slave-descendent.